Risk assessment using ERIN and CVL methods to minimize musculoskeletal disorders for operators in the food industry - Muslimah, Etika; Nandiroh, Siti; Faizi, Ahmad Nur; Munawir, Hafidh; Fahmi, Afiqoh Akmalia (OPSI, 2025)
Workers in small-scale industries often experience physical fatigue and musculoskeletal complaints during manual production activities. This research focuses on operators in a Small and Medium Enterprise (SME) producing cowhide crackers, where symptoms of Musculoskeletal Disorders (MSDs) are commonly reported. The purpose of this study is to identify the level of worker discomfort, assess the likelihood of MSD occurrence, and determine appropriate recommendations to reduce ergonomic risk. The Nordic Body Map (NBM) was used to identify complaint areas, Cardiovascular Load (CVL) was employed to assess physical workload intensity, and the ERIN method was applied to evaluate postural risk. The NBM results showed high discomfort levels at the boiling and frying workstations, with scores of 81 and 76.3, respectively. CVL findings also indicated elevated workload at the same stations, with values of 45% and 38%, suggesting fatigue and the need for improvement. Meanwhile, the ERIN assessment showed medium postural risk in one frying activity, low risk in two sub-activities, and high risk in two boiling sub-activities. As a result, a redesign of tools and workstation layout was proposed and simulated using CATIA. The simulation results demonstrate a reduction in MSD risk, where the ERIN score decreased from 34 (high) to 14 (low), confirming the effectiveness of the redesigned workstation.